Functional Activity of Rat Adrenocorticocytes after Incubation in Dimethyl Sulfoxide Based Cryoprotective Media Supplemented with Fetal Bovine Serum - Yurchuk, Taisiya A.; Bozhok, Galina A.; Alabedalkarim, Natalia M.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2014)
Investigation of functional state of cells at various stages of cryopreservation is important for the development and improvement of freezing protocols of endocrine cells. This study assessed the effect of incubation in media with 5, 7, 10, and 15% dimethyl sulfoxide (DMSO), as well as the media with DMSO and 25% fetal bovine serum (FBS) on some indices of adrenal cortex cell suspension: viability (MTT-test), content of cells with active 3b-hydroxysteroid dehydrogenase, functionally active mitochondria (JC‑1 test), as well as the level of basal and stimulated aldosterone secretion. It was shown that presence of FBS in a cryoprotective medium reduced the toxic effect of DMSO on adrenocorticocytes during incubation, furthermore in some cases incubation in media with DMSO and FBS led to the increase in the number of cells with functionally active mitochondria and cells with active steroidogenesis if compared with the suspensions with cells not exposed to cryoprotectant solution. Probl Cryobiol Cryomed 2014; 24(1):47–56.